Registration of 'S11‐16653C' soybean: A high‐yielding conventional cultivar with broad resistance to diseases and nematodes. Issue 1 (2nd December 2022) - Shannon, G.; Chen, P.; Lee, Y.‐C.; Canella Vieira, C.; Ali, M. L.; Lee, D.; Scaboo, A.; Crisel, M.; Smothers, S.; Clubb, M.; Nguyen, H. T.; Li, Z.; et al.
Abstract: The soybean [ Glycine max (L.) Merr] line S11‐16653C (Reg. no. CV‐554, PI 700000) was developed and released as a cultivar by the University of Missouri, Fisher Delta Research, Extension, and Education Center (MU‐FDREEC). S11‐16653C is an early maturity group V (relative maturity 5.3), high‐yielding conventional (non‐genetically modified) cultivar with determinate growth habit. It is a chloride excluder and has a broad disease resistance package, including soybean cyst nematode ( Heterodera glycines Ichinohe) races 1 (HG type 2.5.7), 2 (HG type 1.2.5.7), 3 (HG type 5.7), 5 (HG type 2.5.7), southern root‐knot nematode [ Meloidogyne incognita (Kofold & White) Chitwood], peanut root‐knot nematode [ Meloidogyne arenaria (Neal) Chitwood], reniform nematode ( Rotylenchulus reniformis Linford & Oliveira), stem canker ( Diaporthe aspalathi Jansen, Castlebury & Crous), Phytophthora root rot (caused by Phytophthora sojae M.J.Kaufmann & J.W.Gerdemann), and sudden death syndrome ( Fusarium virguliforme O'Donell & T. Aoki). S11‐16653C was tested in 78 locations across nine states (Alabama, Arkansas, Kansas, Louisiana, Missouri, Mississippi, North Carolina, Tennessee, and Virginia) from 2012 to 2016. It was entered in internal yield tests at the MU‐FDREEC (2012–2014), USDA Uniform Soybean Tests (2014–2016), and soybean state variety tests (2015). It showed consistent high‐yielding performance and broad adaptability throughout the trials and locations. Overall, S11‐16653C is a high‐yielding conventional soybean cultivar that has potential for commercial production and serves as an exceptional germplasm for soybean breeding. Core Ideas: S11‐16653C is a high‐yielding conventional (non‐genetically modified) soybean cultivar. S11‐16653C has broad disease resistance. S11‐16653C is well adapted in the mid‐southern United States.